Revisiting the Determinants of Productivity Growth : What's new? - Loko, Boileau (IMF Working Papers; Working Paper ;, 2009)
This paper studies the main determinants of total factor productivity (TFP) growth using principal component analysis and a dynamic panel data model and, through a case study, explores key areas where accelerated reforms in the Maghreb countries would boost TFP gains. The results reveal that reforms targeted at attracting foreign direct investment and rationalizing government size, shifting resources from low-productivity sectors to higher ones, and encouraging women to enter the work force, could accelerate TFP gains. Equally important are reforms aimed at strengthening human capital, increasing the volume of trade, and improving the business environment.